2014
DOI: 10.1155/2014/850109
|View full text |Cite
|
Sign up to set email alerts
|

Encephalopathy and Neuropathy due to Glue, Paint Thinner, and Gasoline Sniffing in Trinidad and Tobago-MRI Findings

Abstract: A 29-year-old male petrol station pump attendant was admitted with ataxia and clinical evidence of a sensorimotor polyneuropathy which developed over the preceding 3 months. He had cognitive dysfunction, hearing loss, and cerebellar clinical abnormalities that came on slowly over the three years. He had a fifteen-year history of sniffing mostly glue, occasionally paint thinners, and, in the recent two years, gasoline. Magnetic resonance brain imaging showed abnormalities of the cerebral cortex, cerebral white … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Time series of the fMRI data were decomposed on six levels using the maximum overlap discrete wavelet transform (MODWT), which allows signal decomposition at different resolution levels using the Daubechies least asymmetric wavelet filter (8). The decomposition was carried out with the R package brainwaver 1.6.…”
Section: Time Series Extraction and Graph Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…Time series of the fMRI data were decomposed on six levels using the maximum overlap discrete wavelet transform (MODWT), which allows signal decomposition at different resolution levels using the Daubechies least asymmetric wavelet filter (8). The decomposition was carried out with the R package brainwaver 1.6.…”
Section: Time Series Extraction and Graph Calculationmentioning
confidence: 99%
“…Several clinical investigations in adults, including those in subjects with chronic job-related industrial solvent exposure, have shown that chronic use of inhalants is associated with significant brain abnormalities. Among the most commonly reported effects are leukoencephalopathy (6,7) and atrophy of both the cerebellum and corpus callosum (8). It is worth mentioning that inhalants are commonly one of the earliest drugs used by adolescents, and a few authors have pointed out that such encephalopathies can be observed in young consumers (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Solvent abuse can result in neurological disorders, including psychiatric diseases such as depression, anxiety, bipolar mood disorder, and addiction (Ridenour et al, 2007 ). The long-term exposure to organic solvents may also produce chronic encephalopathy, which is characterized by abnormalities in brain structures and cognitive dysfunction (Ramcharan et al, 2014 ).…”
mentioning
confidence: 99%
“…Usually, commercial solvent abuse results in exposure to several volatile substances, such as toluene, n -hexane, xylene and benzene. This makes it difficult to study the neurotoxic effects of the individual constituents (Ramcharan et al, 2014 ). Therefore, researchers have to study the effects of each solvent to clarify their role in brain degeneration and neurological impairment.…”
mentioning
confidence: 99%
See 1 more Smart Citation